A mestizo cosmographer in the New Kingdom of Granada: astronomy and chronology in Sánchez de Cozar Guanientá¿s Tratado (c.1696) (2021)
ABSTRACT: This article interprets a recently recovered manuscript, Tratado de astronomía y la reformaçión del tiempo, composed by Antonio Sánchez in New Granada c.1696, in the context of the Spanish and Renaissance cosmographies. Sánchez’s Tratado proposes a spherical astronomy, in which celestial bodies – including comets — move in orbs containing pyramidal knots that explain the changing speed observed in the motion of planets. From this astronomy and following the peninsular style of repertorios, Sánchez derives two major conclusions: the corrected length of the solar year and a revised birth date of Jesus. Taking as center of reference Vélez, where Sánchez was based, these claims led to conclusions in domains ranging from calendric astronomy to eschatology, including the incorporation of the indigenous peoples into salvation narrative and a demonstration of the arrangement of the celestial orbs at the Last Judgment. Sánchez’s Tratado constitutes an expansion of the Spanish mathematical cosmography that sheds light on the production of knowledge in the Spanish-American world and, at the same time, provides elements to reassess our understanding of the global circulation of Renaissance and early modern ideas.